Surface fluoride management for enhanced stability and efficiency of halide perovskite solar cells via a thermal evaporation method. Issue 24 (23rd May 2022) - Gu, Wei-Min; Zhang, Yue; Jiang, Ke-Jian; Yu, Guanghui; Xu, Yanting; Huang, Jin-Hua; Zhang, Yanyan; Wang, Fuyi; Li, Yawen; Lin, Yuze; Jiao, Xinning; Gao, Cai-Yan; et al.
Abstract : Phenethylammonium fluoride is conformally coated on a perovskite film via a simple thermal evaporation approach at low temperatures and normal pressure, passivating the defects and reinforcing the structural stability. Abstract : Halide perovskites are highly promising semiconductors for photovoltaics due to their high efficiency and simple solution processing. However, their halide-terminated surface is unstable due to the low binding energy of the Pb–I bond in the perovskites, which allows for surface defect formation and ion migration under external stresses, deteriorating the performance of perovskite solar cells (PSCs). Here, phenethylammonium fluoride (PEAF) is deposited on a perovskite film with controlled thickness via a fast thermal evaporation method at low temperatures and normal pressure, passivating the commonly existing surface halide vacancies without destabilizing the underlying perovskite and sacrificing charge transport in the PSC. Moreover, the fluoride anion in PEAF could undergo a strong interaction with the perovskites due to its high electronegativity, effectively reinforcing the structural stability of the perovskite film. The PEAF-treated PSCs exhibit high power conversion efficiency (PCE) of 23.2% with significantly enhanced stability.